New rhenopyrgid edrioasteroids (Echinodermata) and their implications for taxonomy, functional morphology, and paleoecology. (January 2020) - Ewin, Timothy A. M.; Martin, Markus; Isotalo, Phillip; Zamora, Samuel
Abstract: Rhenopyrgids are rare, turreted edrioasterid edrioasteroids from the lower Paleozoic with a distinctive and apparently conservative morphology. However, new, well-preserved rhenopyrgid edrioasteroid material from Canada, along with a review of described taxa, has revealed broader structural diversity in the oral surface and enabled a re-evaluation of rhenopyrgid functional morphology and paleoecology. The floor plates in Rhenopyrgus viviani n. sp., R . coronaeformis Rievers, 1961 and, R . flos Klug et al., 2008 are well fused to each other and the interradial oral plate and lack obvious sutures, thereby forming a single compound interradial plate. This differs from other rhenopyrgids where sutures are more apparent. Such fused oral surface construction is only otherwise seen in some derived edrioblastoids and in the cyathocystids, suggesting homoplasy. Our analysis further suggests that the suboral constriction could contract but the flexible pyrgate zone could not. Thus, specimens apparently lacking a sub-oral constriction should not necessarily be placed in separate genera within the Rhenopyrgidae. It also supports rhenopyrgids as epifaunal mud-stickers with only the bulbous, textured, entire holdfasts (coriaceous sacs) anchored within the substrate rather than as burrow dwellers or encrusters. Rhenopyrgus viviani n. sp. is described from the Telychian (lower Silurian) Jupiter Formation of Anticosti Island, Québec, Canada and is differentiated by a high degree of morphological variability of pedunculate plates, broader oral plates, and narrower distal ambulacral zones. Specimens lacking or with obscured diagnostic plates from the Ordovician of Montagne Noire, France, and the Ordovician and Silurian of Girvan, Scotland are also described. UUID: http://zoobank.org/7f81d67f-4155-4719-8a45-b278ad70739d